Identification of IRF-associated molecular subtypes in clear cell renal cell carcinoma to characterize immunological characteristics and guide therapy - Chen, Can; Chen, Lin-Yuan; Yang, Rui-Xia; Zhang, Jie-Xin; Shao, Peng-Fei; Xu, Hua-Guo (Frontiers in Oncology, 2023)
Background Recently studies have identified a critical role for interferon regulatory factor (IRF) in modulating tumour immune microenvironment (TME) infiltration and tumorigenesis. Methods Based on IRF1-9 expression profiles, we classified all ccRCC samples into three molecular subtypes (clusters A-C) and characterized the prognosis and immune infiltration of these clusters. IRFscore constructed by principal component analysis was performed to quantify IRF-related subtypes in individual patients. Results We proved that IRFscore predicted multiple patient characteristics, with high IRFscore group having poorer prognosis, suppressed TME, increased T-cell exhaustion, increased TMB and greater sensitivity to anti- PD-1/CTLA-4 therapies. Furthermore, analysis of metastatic ccRCC (mccRCC) molecular subtypes and drug sensitivity proved that low IRFscore was more sensitive to targeted therapies. Moreover, IRFscore grouping can be well matched to the immunological and molecular typing of ccRCC. qRT-PCR showed differential expression of IRFs in different cell lines. Conclusions Evaluating IRF-related molecular subtypes in individual ccRCC patients not only facilitates our understanding of tumour immune infiltration, but also provides more effective clinical ideas for personalised treatment.